Medical Surge Capacity in Atlanta-Area Hospitals in Response to Tanker Truck Chemical Releases. (6th November 2015) - Harris, Curtis; Bell, William; Rollor, Edward; Waltz, Tawny; Blackwell, Pam; Dallas, Cham
ABSTRACT: Objective: We designed and conducted a regional full-scale exercise in 2007 to test the ability of Atlanta-area hospitals and community partners to respond to a terrorist attack involving the coordinated release of 2 dangerous chemicals (toluene diisocyanate and parathion) that were being transported through the area by tanker truck. Methods: The exercise was designed to facilitate the activation of hospital emergency response plans and to test applicable triage, decontamination, and communications protocols. Plume modeling was conducted by using the Defense Threat Reduction Agency's (DTRA) Hazard Prediction and Assessment Capability (HPAC) V4 program. The scenario went through multiple iterations as exercise planners sought to reduce total injuries to a manageable, but stressful, level for Atlanta's health care infrastructure. Results: Atlanta-area hospitals rapidly performed multiple casualty triage and were able to take in a surge of victims from the simulated attack. However, health care facilities were reticent to push the perceived manageable numbers of victims, and scenarios were modified significantly to lower the magnitude of the simulated attack. Additional coordination with community response partners and incident command training is recommended. Security at health care facilities and decontamination of arriving victims are two areas that will require continued review. Conclusion: Atlanta-area hospitals participated in an innovative regional exercise that pushed facilities beyond traditional scopes of practice and brought together numerous health care community response partners. Using lessons learned from this exercise coupled with subsequent real-world events and training exercises, participants have significantly enhanced preparedness levels and increased the metropolitan region's medical surge capacity in the case of a multiple casualty disaster. ( Disaster Med Public Health Preparedness . 2015;9:681–689)